Time course of conflict processing modulated by brief meditation training - Fan, Yaxin; Tang, Yi-Yuan; Tang, Rongxiang; Posner, Michael I. (Frontiers in Psychology, 2015)
Resolving conflict is a pivotal self-control ability for human adaptation and survival. Although some studies reported meditation may affect conflict resolution, the neural mechanisms are poorly understood. We conducted a fully randomized 5 hours trial of one form of mindfulness meditation - Integrative Body-Mind Training (IBMT) in comparison to a relaxation training control. During the Stroop word-color task, IBMT group produced faster resolution of conflict, a smaller N2 and an earlier and larger P3 component of the event-related brain potentials (ERPs). These results indicate that brief meditation training induces a brain state that improves the resolution of conflict.